Pengembalian Keuangan Negara Perkara Korupsi Melalui Eksekusi Integral Oleh Kejaksaan - Lutfy Resli (Faculty of Law, Universitas Lampung, 2020)
The Prosecutor's Office has obstacles and obstacles in carrying out additional criminal executions in the payment of money in lieu of corruption cases which resulted in many arrears in corruption case executions. The Prosecutor's Office made efforts to recover state finances through policies in an integrated manner so that they could carry out criminal executions of replacement money. This research uses the normative juridical approach and empirical juridical approach. Then the data analysis is done qualitatively which then draws conclusions that are inductive. Based on the results of the study, the return of state finances in corruption cases is carried out through an integral execution policy of the Prosecutor's Office in criminal law which cannot be carried out using the provisions of Article 18 of the Corruption Law. Constraints on the financial return of the state of corruption cases through integral execution by the Prosecutor's Office in the previous law due to the non-stipulation of procedures for carrying out additional criminal executions in the form of payment of replacement money. Suggestions in this research are efforts to recover state finances through the execution of additional substitute penalties suggested by taking the civil route then the government immediately enacted the asset seizure bill in order to facilitate prosecutors carrying out criminal executions in the case of corruption and make forgiveness policies to bleach payment of replacement money for convicted persons..